Alveolar ridge augmentation with the perforated and nonperforated bone grafts - Avila, Erica Dorigatti de [UNESP]; Scarso Filho, José [UNESP]; Oliveira Ramalho, Lizete Toledo de [UNESP]; Real Gabrielli, Mario Francisco [UNESP]; Pereira Filho, Valfrido Antonio [UNESP] (Korean Acad Periodontology, 2014)
Purpose: Autogenous bones are frequently used because of their lack of antigenicity, but good osteoconductive and osteoinductive properties. This study evaluated the biological behavior of perforated and nonperforated cortical block bone grafts.Methods: Ten nonsmoking patients who required treatment due to severe resorption of the alveolar process and subsequent implant installation were included in the study. The inclusion criteria was loss of one or more teeth; the presence of atrophy of the alveolar process with the indication of reconstruction procedures to allow rehabilitation with dental implants; and the absence of systemic disease, local infection, or inflammation. The patients were randomly divided into two groups based on whether they received a perforated (inner surface) or nonperforated graft. After a 6-month healing period, a biopsy was performed and osseointegrated implants were installed in the same procedure.Results: Fibrous connective tissue was evident at the interface in patients who received nonperforated grafts. However, full union between the graft and host bed was visible in those who had received a perforated graft.Conclusions: We found that cortical inner side perforations at donor sites increased the surface area and opened the medullary cavity. Our results indicate an increased rate of graft incorporation in patients who received such perforated grafts.
Keywords: Alveolar ridge; Autografts; Dental implants; Oral surgery